CURRENT RATIO DAN LEVERAGE RATIO DALAM MEMPERGARUHI PROFITABILITAS PADA PT. ASTRA INTERNASIONAL TBK. PERIODE 2014-2023 - Apinus Gani; Ayu Puspa Lestiyadi (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the effect of Current Ratio (CR) and Leverage Ratio Debt to Equity Ratio (DER) ) on profitability measured using Return on Assets (ROA) at PT. Astra International Tbk. for the period 2014-2023. This type of research is quantitative using secondary data in the form of financial reports. The results of this study indicate that partially Current Ratio has a significant negative effect on Return on Assets. These results are indicated by the value (T count > T table) (-5.247 > 1.8945) Debt to Equity Ratio (DER) has no effect on Return on Assets (ROA). These results are proven by (T count <T table) (568 <1.8945). Simultaneously Current Ratio and Debt to Equity Ratio have an effect on Return on Assets. The results of this study are supported by the (F- count > F-table) (18.572 > 4.74). This study concludes the need for more optimal financial management and consideration of other factors influencing a company's financial performance. This research provides theoretical and practical benefits for the development of financial management science and investment decision-making.